Plant community analysis and effect of environmental factors on the diversity of woody species in the moist Afromontane forest of Wondo Genet, South Central Ethiopia - Kebede, Mamo; Yirdaw, Eshetu; Luukkanen, Olavi; Lemenih, Mulugeta (Biodiversity: Research and Conservation, 2013)
Floristic diversity and the composition of vascular plants are described for the moist Afromontane forest (MAF) of Wondo Genet, south-central Ethiopia. A total of 75 (20 x 20 m) quadrats were sampled and data on species identity, abundance, elevation, slope and aspect were recorded. Different diversity indices and ordination techniques were used to analyze the data. A total of 240 plant species including seven endemic plant species were found representing 94 families and 210 genera, of which trees constitute 23.8%, shrubs 25%, herbs 35%, lianas 11.3% and ferns 5%. Cluster and indicator species analyses revealed five plant communities described as: Teclea nobilis-Calpurnia aurea, Erythrococca trichogyne-Millettia ferruginea, Croton macrostachyus-Vernonia hochstetteri, Protea gaguedi-Rhus retinorrhoea and Dodonaea angustifolia-Hypericum quartinianum. Elevation (R2=0.48, P<0.001), slope (R2=0.14, P<0.001) and aspect (R2=0.04, P<0.01) correlated significantly and negatively with species richness, whereas only elevation (R2=0.30, P<0.001) and slope (R2=0.13, P<0.001) related significantly and negatively with abundance. Sørensen’s similarity coefficient indicates that the forest of Wondo Genet is similar to moist montane forests of southwestern and southeastern Ethiopia. Given the high diversity, coupled with the existence of endemic species, ecosystem conservation and restoration strategies with further research are warranted.